Addition and elimination reactions of aliphatic compounds - Bamford, C. H.; Tipper, C. F. H. (Charles Frank Howlett) (Comprehensive chemical kinetics ;, 1973)
Addition and Elimination Reactions of Aliphatic Compounds.